Gender-diverse boards, liquidity, and financial distress: Pathways to fraud deterrence in auditor judgments - Arifin, Aulia Lestari; Koerniawan, Koenta Adji (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the effect of board gender diversity and liquidity on going concern audit opinions, with financial distress serving as a mediating variable. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study analyzes panel data from 84 observations of non-financial Indonesian SOEs between 2020 and 2023. The findings reveal that both board gender diversity and liquidity significantly influence going concern audit opinions, with financial distress mediating the effect of liquidity but not gender diversity. Liquidity also significantly impacts financial distress. These results underscore the importance of governance and financial indicators in shaping audit judgments. The study contributes to fraud deterrence literature by linking strong liquidity and diverse boards to reduced audit risk. Practical implications include encouraging regulators to mandate board diversity in SOEs and promoting liquidity management as a fraud prevention mechanism. Auditors are advised to integrate governance indicators when assessing business continuity risk.